Realizing strong visible-light absorption band for 2D crystalline carbon nitride sheets induced by extending π-conjugation and introducing cyano groups. (March 2022) - Wang, Yong; Sun, Mei; Tang, Wenchao; Li, Qikun; Ren, Zewei; Liu, Yichen; Zhang, Yu; Zeng, Chengxin; Wang, Zhenni; Wu, Yizhang; Hao, Jian; Wu, Xiaoshan; et al.
Abstract: Increasing the visible-light absorption of atomically thin two-dimensional (2D) materials has long been pursued the understanding of their optoelectronic properties. However, conventional methods usually introduced a tail-like absorption band that significantly affected photocatalysis performance and restricted their practical applications. Here, we observed an unusual strong visible-light absorption band in crystalline carbon nitride sheets (CNs) without introducing the tail-like absorption band. The experimental results and density functional theory calculations revealed the new mechanism: (i) π-conjugated system between the heptazine units is extended in modulated CNs, (ii) the visible-light absorption band of CNs is expanded by introducing cyano groups into the π-conjugated system, and (iii) modulated CNs charge distribution possesses local characteristics that accelerate photogenerated carriers transport. As a result, the H2 rate of this modulated CNs under visible-light irradiation (>420 nm) reached 7.59 mmol h −1  g −1, which is much higher than reported carbon-nitride-based materials. The design and fabrication of wide-bandgap 2D semiconductor materials with a strong visible-light absorption band revealed from this work has important implications for solar energy conversion. Graphical abstract: A strong visible-light absorption band in crystalline CNs without introducing the tail-like visible-light absorption using molten salts is reported. The photocatalyst based on this material shows a much superior visible-light photocatalytic activity. Image 1 Highlights: The visible-light absorption band of CNs can be expanded by introducing cyano groups into the π-conjugated system. Increasing the local fluctuations of the electrostatic potential helped separate the photoexcited electron-hole pairs. The photocatalyst based on this material shows a much superior visible-light photocatalytic activity.